A maritime community with a shared future: bridging fragmented legal regulations for marine plastic pollution - Liu, Zhao (Frontiers in Marine Science, 2025)
Marine plastic pollution highlights the limitations of fragmented governance regimes. This study proposes the Maritime Community with a Shared Future (MCSF) as a framework to address this challenge. Through comparative legal analysis of treaty conflicts and case studies of the INC process, we demonstrate that the MCSF and the proposed global plastics treaty are designed to have a symbiotic relationship, rather than a competitive one. This research provides a negotiation pathway for the global plastics treaty.